Synthesis, characterization, and hydrolytic degradation of polylactide/poly(ϵ-caprolactone)/nano-silica composites. Issue 11 (2nd November 2017) - Liu, Yangshuo; Liu, Guoyu; Li, Ming; He, Chiyang
ABSTRACT: Poly(lactic acid) (PLA)/poly(ϵ-caprolactone) (PCL)/nano-silica composite degradable films were prepared by a solvent casting method. SEM results showed that the nano-silica particles were dispersed uniformly in the PLA/PCL matrix. TGA results indicated that the thermal decomposition temperature rose with the increase of nano-silica content. The tensile strength of the composites was enhanced with the increase of nano-silica content up to 2%. The tensile strength increased with the silica content and reached its maximum (22.51 Mpa). The improvement in the water uptake ratio in the PLA/PCL/silica nanocomposites may be attributable to the presence of silica nanoparticles in the PLA/PCL matrix. After 15 weeks total processing time for the solution of alkaline and phosphate buffer, the performances of 16.23% and 3.65% for degradation.